Agen Penggerak Permainan Tradisional: Solusi mengurangi Kecanduan Gadget Pada Anak - Jufrida Jufrida; Fibrika Rahmat Basuki; Wawan Kurniawan (Jurnal Surya Masyarakat, 2021)
The use of gadgets can cause addiction and have a negative impact on the health and psychological development of children. The solution to overcome this problem was through outdoor learning based on local wisdom of traditional games. This activity aims to form an agent for driving traditional games to reduce the use of gadgets for children in the District of Pelayangan. The method of implementing activities was in the form of socialization, training and assistance to prospective agents who drive traditional games. The targets of the activities were students at SDN 04 / IV and SDN 10 / IV Jambi City. The activity was carried out in  July-September 2020. The evaluation was carried out by giving questionnaires to participants to determine the success of the activity. The results of this activity indicated that students at SDN 04 / IV and SDN 10 / IV Jambi City preferred traditional games. Based on the results of the questionnaire, data on the frequency of using gadgets decreased from an average of 25 hours/week to 17 hours/week. Through traditional games, students interact more frequently with peers. This activity also increases knowledge about traditional games. This traditional game also trains students' social skills and character such as cooperation, hard work, honesty, sportsmanship, obeying rules, dexterity, accepting defeat, and responsibility.